2013
DOI: 10.1039/c2fo30129f
|View full text |Cite
|
Sign up to set email alerts
|

In vitrolipid digestion of chitinnanocrystal stabilized o/w emulsions

Abstract: Chitin nanocrystals (ChN) have been shown to form stable Pickering emulsions. These oil-in-water emulsions were compared with conventional milk (whey protein isolate, WPI, and sodium caseinate, SCn) protein-stabilized emulsions in terms of their lipid digestion kinetics using an in vitro enzymatic protocol. The kinetics of fatty acid release were evaluated as well as the change in oil droplet size of the respective emulsions during lipid digestion. The interfacial pressure was measured by addition of the duode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(80 citation statements)
references
References 48 publications
(71 reference statements)
1
79
0
Order By: Relevance
“…The lipid droplets in conventional emulsion would be coated by a thin monolayer of globular protein molecules, while the droplets in nanoemulsion would be coated by a much thicker layer of aggregated globular protein molecules due to the shrinkage of the droplets during their preparation by solvent evaporation [3]. Particle-stabilized interfaces also offer a promising template for controlling interfacial displacement by bile salts and thus lipid digestion, as was reported for chitin nanocrystals [10]. Sarkar et al revealed that the heat-induced microgel particle could achieve an increased coverage-fused network at the oil-water interface, which was more efficient in delaying the rate of lipid digestion compared to the intact whey protein microgel particles [11].…”
Section: Introductionmentioning
confidence: 96%
“…The lipid droplets in conventional emulsion would be coated by a thin monolayer of globular protein molecules, while the droplets in nanoemulsion would be coated by a much thicker layer of aggregated globular protein molecules due to the shrinkage of the droplets during their preparation by solvent evaporation [3]. Particle-stabilized interfaces also offer a promising template for controlling interfacial displacement by bile salts and thus lipid digestion, as was reported for chitin nanocrystals [10]. Sarkar et al revealed that the heat-induced microgel particle could achieve an increased coverage-fused network at the oil-water interface, which was more efficient in delaying the rate of lipid digestion compared to the intact whey protein microgel particles [11].…”
Section: Introductionmentioning
confidence: 96%
“…To date, a limited number of these food-grade Pickering particles have been reported in the literature, which encompass modified starch (Karger, Fayazmanesh, Alavi, Spyropoulos, & Norton, 2012;Tan et al, 2012), chitin nanocrystal particles (Tzoumaki, Moschakis, Kiosseoglou, & Biliaderis, 2011;Tzoumaki, Moschakis, Scholten, & Biliaderis, 2013), waterinsoluble zein (de Folter, van Ruijven, & Velikov, 2012), microcrystalline cellulose (MMC) (Karger et al, 2012), solid lipid nanoparticles (Gupta & Rousseau, 2012), and more recently, proteinbased particles or nanoparticles from whey protein (Destribats, Rouvet, Gehin-Delval, Schmitt, & Binks, 2014;Shimoni, Levi, Levi Tal, & Lesmes, 2013) and soy or pea protein isolate (Liang & Tang, 2014;Liu & Tang, 2013. Among these particles, colloidal particles or nanoparticles from food proteins seem to be most promising to perform as Pickering stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the case of heat-treated whey protein isolate-stabilized emulsions, bile salts are known to create defects in the protein network at the cross-linked interface and thus access to lipase is established 18,46 . Both WPI and heat treated WPIstabilized emulsions generated approximately 46% of FFAs derived from the long-chain FFAs from sunflower oil that tend to activity 21,36 . However, in case of WPM and HT-WPM stabilized emulsions, the extent of fatty acid release was slightly lower than the WPI emulsions (46%) generating approximately 42% of FFAs.…”
Section: In Vitro Intestinal Digestion and Free Fatty Acid Release Kimentioning
confidence: 99%
“…Simplistically, one might expect lipid digestion to be controlled by strengthening the interfacial network that resists displacement by bile salts. Therefore, particle-stabilized interfaces offer a promising template for controlling displacement by bile and therefore lipid digestion, with the first evidence being reported on chitin nanocrystals 21 . If proven, Pickering emulsions could be used to address site-dependent controlled release of nutrients, drugs or bioactive moieties in food, pharmaceutical and personal care applications.…”
Section: Introductionmentioning
confidence: 99%